PENGARUH ATMOSFIR TOKO, LOKASI TOKO DAN DISPLAY PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI TOKO KELONTONG SRC HENDRO - Muinah Fadhilah; Agus Dwi Cahya; Herman Setiawan (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
This study aims to determine the effect of store atmosphere, store location, and product display on consumer purchasing decisions at SRC Hendro grocery store. The type of research used is quantitative. The population in this study are all consumers who shop at the SRC Hendro grocery store. The sample of this study amounted to 100 respondents obtained from 5 times the number of research indicators. The results showed that the variable store atmosphere and store location partially had no significant effect on consumer purchasing decisions at the SRC Hendro grocery store. Product display variable partially has a significant effect on consumer purchasing decisions at SRC Hendro grocery store. Simultaneously stated that the store atmosphere, store location, and product display variables had a significant effect on consumer purchasing decisions at SRC Hendro grocery stores. Based on the results of the study, the researchers concluded that: 1. Store atmosphere partially has no significant effect on consumer purchasing decisions. The resulting sig value is 0.206 which is greater than 0.05, an independent variable is said to have a significant effect if the sig value is less than 0.05, 2. Store location partially has no significant effect on consumer purchasing decisions because it has a sig value that is greater than 0.05, namely 0.765, 3. Product display partially has a significant effect on consumer purchasing decisions. This is based on the sig value obtained in data processing of 0.038 which means less than 0.05, 4. The store atmosphere, store location, and product display simultaneously have a significant effect on consumer purchasing decisions, this is based on the sig value obtained in processing data of 0.000 which means less than 0.05.